EDUCATIONAL SYSTEM IN WESTERN AND EASTERN COUNTRIES AND PEDAGOGICAL IDEAS OF FAMOUS SCIENTISTS - Mirzayeva, Shokhidabonu Bakhtiyor qizi (Innovative Development in Educational Activities, 2022)
This article describes the formation of the Western and Eastern educational system, its changes, useful aspects, and pedagogical ideas of famous scientists.